GESTÃO EFICAZ DA TERCEIRIZAÇÃO NA MANUTENÇÃO INDUSTRIAL PARA GARANTIR QUALIDADE, EFICIÊNCIA E PRODUTIVIDADE - Tavares, Alexandre Dias (2014)
In this work we go to present some suggestions for definition of where and when to apply the outsourcing inside of the maintenance area and that resulted they can be waited. To allow the conduction of the subject, the criteria of definition of criticality of the assets of an industrial installation and of services will be boarded, therefore the outsourcing strategy passes for the recognition of this variable. Also recommendations for elaboration of outsource contracts of form will be presented to prevent labor demands of the employees of third against the contracting company. We will indicate some variants of the process of outsourcing using companies specialized in contract administration of this nature and the use of used services of the proper ones of the contractor that are stimulated to form independent companies for specialized rendering of services being generated the sustainability of the process for the expansion of its activities for other companies.